Learners' attitude towards learning through CD-ROM courseware : a case study of an organization. - Muhamad, Mazanah; Mansor, Ahmad Zamri; On Lily, (Journal of International Management Studie, 2010)
The paper seeks to explore two factors associated with learners’ attitude toward learning through CD-ROM courseware: (1) learners’ characteristic; and (2) characteristics of CD-ROM courseware. Data were administered using an instrument custom designed for the study. The respondents were 150 employees of the selected organisation who had used any CD-ROM courseware in any of the organisation’s learning centres during a specified one-month period. Results show that: (1) the majority of respondents surveyed found to have favourable attitude toward the last CD-ROM courseware they had used; (2) learners’ attitude towards computers was found to be highly correlated with learners’ attitude towards CD-ROM courseware; and (3) courseware characteristics of textology and immediate feedback were identified as two of the most highly correlated factors. In learning through CD-ROM courseware, learners’ characteristics such as learners’ attitude towards computers, their working experience and educational achievement need to be taken into consideration. In CD-ROM courseware development, characteristics such as textology and immediate feedback are important elements that facilitate positive attitude towards learning. This study is useful to CD-ROM courseware developers and training managers in developing a more appropriate training for learners.